Studies of DNA interactions with functionalized benzo[a]phenoxazinium chlorides - Raju, B. Rama (2012)
The interaction with DNA phosphate of a series of water-soluble benzo[a]phenoxazinium chlorides mono- or disubstituted with 3-chloropropyl groups at the amine of position 9, and also at the oxygen of position 2, was investigated. It was found that the type of substitution on the polycyclic system and the nature of terminal groups have a remarkable influence on the kind of interaction of these NIR fluorophores and an additional emission band was detected near 570 nm.